The influence of key parts of hydraulic roof cutting and roof fracture behavior in mining roadway - Yukun LIN; Jiangwei LIU; Yaoyou LIU; Changyou LIU (Meitan xuebao)
Dynamic pressure roadway often has problems such as serious deformation of roadway and di-fficult control of surrounding rock. The large deformation of dynamic pressure roadway is usually related to the characteristics of surrounding rock and the stress environment formed by the superposition of dy-namic and static loads. The mining roadway of No.5 coal seam in Huairen Zhifengshan Coal Mine in S-hanxi adopted the tunneling method of facing mining, there was a problem of confrontation between the tunneling working face and the mining working face. Large deformations caused by mining intersections that could result in destabilisation of the perimeter rock structure of the adjacent working face roadway, which made the roadway difficult to maintain and seriously restricted the safe and efficient production of coal resources. In view of this, a method of hydraulic fracturing on the stress transfer path was prop-osed to destroy the rock mass structure in the designated area, thereby reducing the stress in the surrou-nding rock of the roadway and controlling the stability of the surrounding rock of the roadway. The me-chanical model of rock beam at the fracture site of hard rock strata was constructed. The relationship b-etween the position of hydraulic roof cutting and the bending elastic energy of roof and the subsidence rate of roof was calculated by the physical and mechanical parameters of rock mass in Zhifengshan Coal Mine, and the influence of the fracture site of hard roof on the fracture behavior was analyzed. Combi-ned with field engineering verification, the mechanism of large deformation of mining and excavation ro-adway was revealed, and the reasonable fracturing position was determined. The results show that hydra-ulic fracturing and roof cutting pressure relief in the key parts of hard rock strata can destroy the stress transfer path, reduce the stress superposition effect of overlying strata, and control the rate of energy r-elease of roof. The cumulative deformation of surrounding rock of roadway after fracturing is generally reduced by 40%-60%, indicating that hydraulic roof cutting in the key parts realizes the effective cont-rol of surrounding rock of mining and excavation confrontation roadway, and effectively solves the probl-em of large deformation of surrounding rock instability near roadway. The theoretical results can guide the field construction and confirm the reliability of the model.